CONCERNING THE DEFINITION OF A TERM “PARTICIPATION” IN THE CONTEXT OF CONTEMPORARY ARTISTIC PRACTICES / К ОПРЕДЕЛЕНИЮ ТЕРМИНА «ПАРТИЦИПАЦИЯ» В КОНТЕКСТЕ СОВРЕМЕННЫХ ХУДОЖЕСТВЕННЫХ ПРАКТИК - DENIKIN ANTON A. / ДЕНИКИН АНТОН АНАТОЛЬЕВИЧ (Наука телевидения, 2018)
The article examines the concept of “participation” in the context of modern culture and art. It is shown that “participation” becomes a key concept in the examination of social relations and collective ideas, and also finds itself in the economic, political, social and artistic spheres. The definition of the participation is given in different scholarly fields: philosophy, art criticism, economics, politics, sociology, psychology. Participation in the article is perceived as an aesthetic and artistic phenomenon (in the context of non-classical esthetics). The forms of aesthetics of human interactions and activities of the audience-participants are connected with the “aesthetics of the party”, thereby indicating the sphere of active expressiveness of human activity. A number of approaches to the definition of participatory aesthetics linking complicity with the following directions are examined: with avant-garde aesthetics, with the artistic creativity of the artist, with social and democratic processes, as the value of dialogue (and consensus), with politically motivated and socially engaged projects, and participation as a self-sufficient esthetic phenomenon. The conclusion is arrived at from the examined forms of research that the interdisciplinary aspect and the heterogeneity of practices of participation make arguments about the strict specificity and separateness of creative participation in contemporary art and culture problematic. It is indicated that participation (or complicity) as a type of artistic behavior, an instrument of artistic criticism and an instrument of activation of social dialogue makes it possible to reevaluate the traditional esthetic categories. Within the “esthetics of the party” there is a realization of a combination of art, political criticism, subcultural media practice and social public art projects which can be expressive, effective and meaningful.